Relevansi Permainan Tradisional dalam Film Squid Game Terhadap Perilaku Sosial Anak Usia Dini - Wahyuningtyas, Dessy Putri; Noer, Resi Kartika Prasasti (Cetta: Jurnal Ilmu Pendidikan, 2024)
Social behavior is the foundation for children when entering the social world, where children are required to interact with others. The purpose of this research is to find out the similarities of the game in the Squid Game film with traditional games in Indonesia and also to see the social behavior that arises when playing traditional games for early childhood in the Squid Game film. This research uses qualitative research using a library research approach. Data sources are obtained from movies and other supporting sources in the form of literature. The analysis used in this research is content analysis. Content analysis is used to analyze the content of the Squid Game film itself. The findings of this study are that there are components of traditional games in the Squid Game movie, namely: Mugunghwa kkoci pieot seumnida, Juldarigi, Guseul nori, Geonneogi, and Ojingeo geim. The social behavior in the Squid Game film itself is mutual help, cohesiveness, cooperation, demonstration, sportsmanship, discipline, playing together, empathy, respect for others, mutual help, friendship, and solidarity. The relevance of traditional games for early childhood is the relationship between children in playing, traditional games raised in the Squid Game movie can be a learning medium.